The Qur'anic style and its effect on the setting of the fatwa (Journal of the College of Basic Education, 2022)
The style of the Noble Qur’an of its proper organization, its proper interpretation and its accuracy of understanding, and the understanding that the meaning is consistent between the verses that correspond to the necessity of the case, and how these cases are identical to the reasons of the soul, in keeping with the changes of time and place, and as a reference to the calamities and events that the mufti sheltered when needed. Some of the Qur'an's style is influenced by the present fatwa of reality, which is the direction of the Holy Qur'an's methods by conducting, patterns and systems of speech, including the correct meanings and the most accurate connotations, the relation of meaning to their words and its relevance, and the clarification of the requirements of its conditions, from the state of speech and related matter, according to the case and even if it includes sentences. Some of those sentences are related to each other and it is inevitability to the one who understands the response of the last speech to the beginning, and to realize the consistency of meaning between the verses that match the situation, all of which are related to the tools and methods of understanding, which is the middle link between the jurisprudence of the legal speech, its understanding, and the jurisprudence of the speech, in which became what is barely understood into practical, and a personalized practical realism